Effectiveness of synbiotics in obesity management: A literature review - Miftahul Jannah; Prananingrum Kinasih; Dhiya Fadhila Rahmah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
The increased occurrence of obesity worldwide is playing a major role in the growth of serious illnesses, such as Cardiovascular Disease and Type 2 diabetes. Modulation of gut microbiota using synbiotics is a novel alternative. This study provides evidence for the effectiveness of synbiotics in managing obesity, particularly with respect to body composition and anthropometric measurements. This review focuses on the years 2020-2025. Using the keywords “synbiotic” AND “obesity,” criteria based on inclusion and exclusion were applied to the Title, Abstract, and TEXT to screen publications. Data available in English in the specified years were used. Short-term synbiotic supplementation shows little evidence of affecting body weight or body mass index. However, waist circumference, body fat percentage, and visceral fat loss suggest that short-term to mid-term synbiotic supplementation has a more consistent effect on body composition and central obesity. The positive impact of synbiotics is more noticeable when high-fiber diets are used. In conclusion, ulterior to achieving absolute weight loss, it can be concluded that synbiotics are a safe means of managing obesity as a central means of improving body composition and central obesity.